Lexical Relation used in Newspaper Headline of the Jakarta Post: Jokowi Highlights Tolerance at Cultural Congress Conclusion - Nurmayana, Nurmayana; Nasution, Nazlah Syahaf (SALEE: Study of Applied Linguistics and English Education, 2023)
The lexical meaning was the smallest meaning unit in the meaning system of language that could be distinguished from other similar units. A lexeme was an abstract unit that occurred in many different forms of spoken or written sentences. Lexical associations were considered more important in the headline in the newspaper because they formed a semantic relationship and related to the most problematic coherence as open-word in the form of noun and verb since the lexical meaning of the words had the same meaning in the context. This research aimed to examine the use of lexical meaning in the headline newspaper of the Jakarta Post. The result found that there were few words whose lexical meaning correlated to certain semantic roles. As two semantic roles were used in analyzing the data, it was obtained that synonym words existed in 13 words, its percentage toward the article was 3.01%; and hyponymy words existed in 10 words, its percentage toward the article was 2.32%. This result indicated that lexical relations such as synonymy and hyponymy might vary to perform functions between sentences and clauses. Choosing the correct definition of a lexical word could avoid misinterpreting the proposition of the reader’s interpretation. It was determined that the Jakarta Post, especially in the headline entitled “Jokowi highlights tolerance at cultural congress conclusion,” contained mostly synonym words, which meant most of the lexical meaning of the words had the same meaning in the context.